State of the given functions are inverses. Part 3. NO LINKS!!!!
2 answers:
Answer:
9.
h(x)=-x-1
let y =-x-1
interchanging role of x & y
x=-y-1
y=-x-1
h-¹(x)=-x-1
again
f(x)=(2-3x)/2
let
y=(2-3x)/2
interchanging role of x & y
x=(2-3y)/2
2x-2=-3y
y=(2-2x)/3
f-¹(x)=(2-2x)/3
<u>G</u> <u>i</u> <u>v</u> <u>e</u> <u>n</u> <u> </u> <u>f</u> <u>u</u> <u>n</u> <u>c</u> <u>t</u> <u>i</u> <u>o</u> <u>n</u> <u> </u> <u>a</u> <u>r</u> <u>e</u> <u> </u> <u>n</u> <u>o</u> <u>t</u> <u> </u> <u>i</u> <u>n</u> <u>v</u> <u>e</u> <u>r</u> <u>s</u> <u>e</u> <u> </u> <u>o</u> <u>f</u> <u> </u> <u>e</u> <u>a</u> <u>c</u> <u>h</u> <u> </u> <u>o</u> <u>t</u> <u>h</u> <u>e</u> <u>r</u> <u>.</u>
10.
f(x)=-x+3
let y=-x+3
interchanging role of x & y
x=-y+3
y=3-x
f-¹(x)=-x+3
equal to g(x)=-x+3
<u>Given function are</u> <u> inverse of each other.</u>
Answer:
Step-by-step explanation:
Call h(x) = y (It's easier to see).
y = -x - 1
The first step is always to interchange x and y
y = -x - 1
-x = y - 1
Solve for y
-x + 1 = y
If I understand the question, these two (f(x) and h(x)) are not inverses.
10 is a bit tricky. An inverse can invert into itself: This is called an involution. But if they are differently labeled, I'm not sure. I don't think that this is exactly what is men by an involution. Something like y = x would be. But you have 2 different inverses. I'm not sure that this qualifies.
y = x + 3
g = x + 3
x = y + 3
x - 3 = y
You might be interested in
The answer is 16/2 cups of sugar
Answer:
I think its AED19
Step-by-step explanation:
please give brainliest if correct
Answer:
9x-3x(2-4)=6x(3x+4)-6(3x-2)
Hello! Its really simple 16 ounces equal 1 pound!
Answer:
.46
Step-by-step explanation:
If you graph the function, you can see where the two logs intersects. View the image I have attached.